Web-based Project-based Learning to Enhance Arabic Language Skills of Madrasah Aliyah Students - Rahmah, Ikhwanur; Asrowi, Asrowi; Musadad, Ahmad Arif (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The aimed of this study is to analyze the need of learning media, web-based project, as an effort to enhance students' skills in Arabic. This study used descriptive quantitative method. 2 teachers and 15 students in the eleventh-grade are the participants of this study. The data collection techniques used in this study are Arabic language skills tests (speaking, reading, and writing). Data reduction, data presentation, and conclusion presentation are the interactive analytical techniques that used to analyze the results. Based on the results, teachers tended to resist adopting new technologies, using traditional learning media, and using non-project-based teaching materials and methods. Therefore, the initial test results show that students' Arabic language skills were low. It can be concluded that the use of web-based project-based learning will be suitable as a learning media for the process of learning Arabic. The teachers hope that by using this media, students will get more used to practicing their Arabic language skills and improve their skills.